Micro, Small, and Medium Enterprises, Cashless, and Economic Growth: Study In The National Capital City Buffer Area - Nor Rahma Rizka; Fitra Izzadieny; Kristianto Tricahya Prabowo (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
The shift of the National Capital (IKN) in East Kalimantan requires provinces in the Kalimantan region to take proactive steps to support the success of its development by encouraging economic growth. One effective strategy to achieve this is to strengthen the development of green Micro, Small, and Medium Enterprises (MSMEs) that are competitive and sustainable. This study aims to explore and empirically assess the role of MSMEs in encouraging economic growth in the Kalimantan region. This research method uses the technique Moderated Regression Analysis with panel data consisting of data from provinces in Kalimantan for the period 2019-2022. The data collected from the Central Bureau of Statistics, the Department of Industry, Trade, Cooperatives, and SMEs, and the Bank Indonesia. The results of this study indicate that there is a significant influence of MSMEs on economic growth in the Kalimantan Region. In addition, evidence was obtained that cashless able to strengthen the influence of MSMEs on economic growth. So that the central government and regional governments of the provinces in Kalimantan can optimize competitive green MSMEs. This can be done through the development of MSMEs by preparing human resources, policies, supporting infrastructure for non-cash transactions (cashless) in MSMEs in each Kalimantan Regional area.Keywords: cashless, IKN buffer zone, green UMKM, economic growth.